2018
DOI: 10.3390/genes10010006
|View full text |Cite
|
Sign up to set email alerts
|

Daily Regulation of Phototransduction, Circadian Clock, DNA Repair, and Immune Gene Expression by Heme Oxygenase in the Retina of Drosophila

Abstract: The daily expression of genes and the changes in gene expression after silencing the heme oxygenase (ho) gene were examined in the retina of Drosophila using microarray and SybrGreen qPCR (quantitative polymerase chain reaction) methods. The HO decrease in the morning upregulated 83 genes and downregulated 57 genes. At night, 80 genes were upregulated and 22 were downregulated. The top 20 genes downregulated after ho silencing in the morning modulate phototransduction, immune responses, autophagy, phagocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
(77 reference statements)
1
18
0
Order By: Relevance
“…The peak of ho expression at the beginning of the day in the retina protects photoreceptors from DNA damage caused by UV and white light [ 27 , 33 ], whereas the second peak at night controls expression of the immune response genes. The circadian cycling of ho mRNA also affects the expression of clock genes and other processes present in the retina, such as phototransduction, DNA repair, and autophagy [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The peak of ho expression at the beginning of the day in the retina protects photoreceptors from DNA damage caused by UV and white light [ 27 , 33 ], whereas the second peak at night controls expression of the immune response genes. The circadian cycling of ho mRNA also affects the expression of clock genes and other processes present in the retina, such as phototransduction, DNA repair, and autophagy [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The circadian clock maintains daily biological rhythms by controlling the expression of target output genes, and is highly conserved between Drosophila and humans (39). Although the eye is not required for circadian behavior in flies (61,62), many genes are rhythmically expressed in the retina including most of the phototransduction machinery (49,63,64). Here, we report that retina-specific disruption of the circadian clock in Drosophila leads to progressive lightdependent retinal degeneration.…”
Section: Discussionmentioning
confidence: 83%
“…One study revealed that KO mice showed sleep/wake disturbances compared to WT mice and that the autophagy marker LC3-II was decreased in both the olfactory bulbs and hippocampi, suggesting an early onset of autophagy dysregulation in Fus1 KO mice 93 . Heme oxygenase (Ho), whose silencing results in the downregulation of autophagy-related genes in both light and dark phases, is expressed in a circadian manner 94 . FoxOs are tightly controlled by fasting/feeding cycles and can upregulate the expression of ATG14 74 .…”
Section: Indirect Regulation Between Autophagy and The Circadian Rhytmentioning
confidence: 99%